Modelling and analysis of a novel CT-guided puncture robot for lung brachytherapy. (3rd June 2017) - Jiang, Shan; Yuan, Wei; Yang, Yunpeng; Zhang, Daguang; Liu, Ningbo; Wang, Wei
Abstract: In this paper, we present a novel CT-guided needle puncture robot system with seven degree of freedoms. All basic requirements of interventional radiology can be met. To solve the space constraints and compatibility requirement, tendon-sheath transmission is used as the drive mode of the end-effector. According to the kinematics analysis of the robot configuration, the reachable workspace is obtained, which can completely cover the chest of patient. Based on the Jacobian matrix, dimension parameters are optimised for better flexibility and kinematic performance in the workspace. Since respiratory movement will cause real-time motion of the tumour, a method is proposed to decrease the puncture error caused by respiratory movement. And the feasibility of this method is verified by puncture experiment based on independent design of respiratory motion simulation device. It is proved that this method will lead to an increase in the puncture accuracy by 2.4 times. In addition, the CT compatibility of the robot is verified, and the positioning accuracy is also measured through the experiments. Abstract :